THE WARRIOR WITHIN : OWN YOUR POWER TO SERVE, FIGHT, PROTECT, AND HEAL - Vanas, D. J. (New York : Portfolio/Penguin, 2022)
"More than an empowerment manual, The Warrior Within is a call to accomplish the world-changing work you were meant for by tapping into the power of the warrior spirit"
Includes index.
Keywords: Self-actualization (Psychology); Determination (Personality trait); Resilience (Personality trait); Caring